2021
DOI: 10.1039/d0na01002b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Joule-heating behaviours of electrically-heatable carbon-nanotube aerogels

Abstract: Electrically-heatable carbon-nanotube aerogels under Joule-heating using the side–side arrangement and the top–bottom arrangement displaying significantly different heating behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Based on this approach, it is estimated that, at a power input of 120 W, an ultrahigh temperature of around 3000 K is reached in the center of the aerogel monolith, an extremely high value close to the melting point of graphitic carbon allotropes . This steady-state core temperature is almost an order of magnitude higher than for many previously reported aerogel heating studies on GO-derived aerogels (Figure i, Table S2, Supporting Information), ,,,,, mainly due to the high power inputs employed here. It is also worth noting that ultrahigh aerogel heating was achieved here at comparatively low voltage inputs (10 V or lower, Figure i), due to the relatively high graphitic quality and corresponding high electrical conductivity of rGO aerogels (here, σ rGOaeroel = 81 S m –1 ).…”
Section: Resultsmentioning
confidence: 63%
“…Based on this approach, it is estimated that, at a power input of 120 W, an ultrahigh temperature of around 3000 K is reached in the center of the aerogel monolith, an extremely high value close to the melting point of graphitic carbon allotropes . This steady-state core temperature is almost an order of magnitude higher than for many previously reported aerogel heating studies on GO-derived aerogels (Figure i, Table S2, Supporting Information), ,,,,, mainly due to the high power inputs employed here. It is also worth noting that ultrahigh aerogel heating was achieved here at comparatively low voltage inputs (10 V or lower, Figure i), due to the relatively high graphitic quality and corresponding high electrical conductivity of rGO aerogels (here, σ rGOaeroel = 81 S m –1 ).…”
Section: Resultsmentioning
confidence: 63%
“…Recent advancements in understanding the fundamental Joule-heating characteristics of pure nanocarbon aerogels 4,25 have provided a solid basis for further investigations into Joule-heating applications involving hybrid nanoparticle-decorated nanocarbon aerogels. For instance, a pioneering study investigated the use of emulsion-templated reduced graphene oxide (rGO) aerogels to examine fundamental Joule-heating characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of research into the fabrication and investigation of the Joule-heating characteristics of nanocarbon aerogels with centimeter-scale structures. Since the discovery of the Joule-heatable graphene aerogel that can be heated up to 200 °C, at an ultralow voltage of 1 V, with a fast-heating capability of 10 K·s –1 , similar approaches have been adopted in the study of other types of nanocarbon aerogels (e.g., carbon nanotube aerogel, rGO aerogel), resulting in improved heating efficiencies and faster heating kinetics. , Studies on the structure–property relationships of Joule-heatable nanocarbon aerogels showed that high thermal conductivity led to lower Joule-heating efficiency . Interestingly, nanocarbon aerogels loaded with functional inorganic nanoparticles exhibited no detrimental impacts on the Joule-heating performances .…”
Section: Introductionmentioning
confidence: 99%